Tricho-Dento-Osseous Syndrome: Diagnosis and Dental Management - Ola B. Al-Batayneh (International Journal of Dentistry)
Tricho-dento-osseous (TDO) syndrome is a rare, autosomal dominant disorder principally characterised by curly hair at infancy, severe enamel hypomineralization and hypoplasia and taurodontism of teeth, sclerotic bone, and other defects. Diagnostic criteria are based on the generalized enamel defects, severe taurodontism especially of the mandibular first permanent molars, an autosomal dominant mode of inheritance, and at least one of the other features (i.e., nail defects, bone sclerosis, and curly, kinky or wavy hair present at a young age that may straighten out later). Confusion with amelogenesis imperfecta is common; however, taurodontism is not a constant feature of any of the types of amelogenesis imperfecta. Management of TDO requires a team approach, proper documentation, and a long-term treatment and follow-up plan. The aim of treatment is to prevent problems such as sensitivity, caries, dental abscesses, and loss of occlusal vertical dimension through attrition of hypoplastic tooth structure. Another aim is to restore function of the dentition and enhance the esthetics and self-esteem of the patient. This paper proposes treatment approaches that include preventive, restorative, endodontic, prosthetic, and surgical options to management. In addition, it sheds light on the difficulties faced during dental treatment of such cases.